Size-Dependent Bioactivity of Silver Nanoparticles: Antibacterial Properties, Influence on Copper Status in Mice, and Whole-Body Turnover - Skomorokhova EA (Dove Medical Press, 2020)
Ekaterina A Skomorokhova,1,2 Tatiana P Sankova,3 Iurii A Orlov,1 Andrew N Savelev,3 Daria N Magazenkova,3 Mikhail G Pliss,4,5 Alexey N Skvortsov,3 Ilya M Sosnin,1 Demid A Kirilenko,1,6 Ivan V Grishchuk,3 Elena I Sakhenberg,7 Elena V Polishchuk,1,8 Pavel N Brunkov,1,6 Alexey E Romanov,1,6 Ludmila V Puchkova,1– 3 Ekaterina Yu Ilyechova1,2 1International Research Center of Functional Materials and Devices of Optoelectronics, ITMO University, St. Petersburg, Russia; 2Department of Molecular Genetics, Research Institute of Experimental Medicine, St. Petersburg, Russia; 3Higher Engineering Physics School of the Institute of Physics, Nanotechnology and Telecommunications, Peter the Great St. Petersburg Polytechnic University, St. Petersburg, Russia; 4Department of Experimental Physiology and Pharmacology, Almazov National Medical Research Centre, St. Petersburg, Russia; 5Laboratory of Blood Circulation Biophysics, Pavlov First Saint Petersburg State Medical University, St. Petersburg, Russia; 6Center of Nanoheterostructures Physics, Ioffe Institute, Russian Academy of Sciences, St. Petersburg, Russia; 7Laboratory of Cell Protection Mechanisms, Institute of Cytology, Russian Academy of Sciences, St. Petersburg, Russia; 8Telethon Institute of Genetics and Medicine, Pozzuoli, Naples, ItalyCorrespondence: Ekaterina Yu Ilyechova Department of Molecular GeneticsResearch Institute of Experimental Medicine, Acad. Pavlov Street, 12, St. Petersburg 197376, RussiaTel +79217605274Fax +78122322307Email ilichevaey@itmo.ruPurpose: The ability of silver nanoparticles (AgNPs) of different sizes to influence copper metabolism in mice is assessed.Materials and Methods: AgNPs with diameters of 10, 20, and 75 nm were fabricated through a chemical reduction of silver nitrate and characterized by UV/Vis spectrometry, transmission and scanning electronic microscopy, and laser diffractometry. To test their bioactivity, Escherichia coli cells, cultured A549 cells, and C57Bl/6 mice were used. The antibacterial activity of AgNPs was determined by inhibition of colony-forming ability, and cytotoxicity was tested using the MTT test (viability, %). Ceruloplasmin (Cp, the major mammalian extracellular copper-containing protein) concentration and enzymatic activity were measured using gel-assay analyses and WB, respectively. In vitro binding of AgNPs with serum proteins was monitored with UV/Vis spectroscopy. Metal concentrations were measured using atomic absorption spectrometry.Results: The smallest AgNPs displayed the largest dose- and time-dependent antibacterial activity. All nanoparticles inhibited the metabolic activity of A549 cells in accordance with dose and time, but no correlation between cytotoxicity and nanoparticle size was found. Nanosilver was not uniformly distributed through the body of mice intraperitoneally treated with low AgNP concentrations. It was predominantly accumulated in liver. There, nanosilver was included in ceruloplasmin, and Ag-ceruloplasmin with low oxidase activity level was formed. Larger nanoparticles more effectively interfered with the copper metabolism of mice. Large AgNPs quickly induced a drop of blood serum oxidase activity to practically zero, but after cancellation of AgNP treatment, the activity was rapidly restored. A major fraction of the nanosilver was excreted in the bile with Cp. Nanosilver was bound by alpha-2-macroglobulin in vitro and in vivo, but silver did not substitute for the copper atoms of Cp in vitro.Conclusion: The data showed that even at low concentrations, AgNPs influence murine copper metabolism in size-dependent manner. This property negatively correlated with the antibacterial activity of AgNPs.Keywords: silver nanoparticles, copper status, ceruloplasmin, alpha-2-macroglobulin, bile, urine